Naive Bayesian Classifiers for Purposes of Medical Differential Diagnostics - Kondrashova, N.; Pavlov, V. (Індуктивне моделювання складних систем, 2014)
A distinctive feature of this work is grouping naive Bayesian classifiers in the scheme of "one against all" and using the extended features space. Metric and categorial variables are present in the original sample. The scheme of "one vs. all" with the use of other methods of classification gives an improvement in the accuracy of the differential diagnosis on exam sample compared to a single Bayesian classifier, but not in the case of the Naive Bayesian classifiers. The obtained results allow us to compare methods accuracies with such as GMDH and canonical discriminant analysis in solution of classification problem.